The Influence of Fins on Heat Transfer Performance Under Free Convection in Air - Tychanicz-Kwiecień, Maria; Mazur, Aleksandra; Gil, Paweł; Gałek, Rafał (Advances in Mechanical and Materials Engineering, 2019)
The article presents preliminary results of thermal parameter measurements of an air-water tubular heat exchanger made of smooth- and finned pipes. The experimental set-up is the equipment of The Department of Thermodynamics at Rzeszow University of Technology. The following parameters have been measured as a function of temperature difference between inlet water temperature and ambient temperature: dissipated thermal power for smooth- and finned pipes and the heat transfer coefficient for a smooth pipe related to the external surface and heat transfer coefficient for a finned pipe related to the overall finned surface. The results indicate that dissipated thermal power increased almost three times for the finned pipe with regard to the smooth pipe. The heat transfer coefficient obtained for a smooth pipe was considerably greater than for a finned pipe.